Ski Slope Security – a new method to help defining the level of difficulty - Garcia, Raul Ressano (2017)
Each ski slope has a color associated with it. These colors are used to inform the skiers about the difficulty level of the ski slope. The aim of this paper is to help improving the ski slope security by proposing a new method to define the color of a ski slope. Defining and informing the ski slope difficulty, is very important to advice skiers to do not go where they are not prepared to go, avoiding injuries and life lost. By proposing this new method we intent to reduce the subjectivity inherent to the classification of the ski slope. This way it is possible to achieve a bigger normalization on the classification and increase the security of the ski slopes